THE DETERMINANTS OF DIVIDEND POLICY: A STUDY OF FOOD AND BEVERAGE MANUFACTURING SECTORS COMPANIES IN INDONESIA - Suhono, Kristian Nugroho; Dewi, Nurma Gupita (Jurnal Ilmiah Akuntansi Indonesia, 2024)
A dividend policy is a management strategy used to decide how much profit the firm will make over a given time period. It's fascinating to watch the peculiar phenomena of dividend distribution inconsistency. The purpose of this study is to investigate the variables—profit growth, collateralizable assets, and investment opportunity set—that affect dividend policy. The methodology for this study is quantitative descriptive. Food and beverage firms that paid dividends between 2020 and 2022 make up the research sample. The sampling method used is called purposeful sampling. Multiple linear regression analysis is the method of data analysis employed. The research findings indicate that dividend policy is positively and significantly impacted by the investment opportunity set. Conversely, the company's growth rate has a notable and adverse impact on dividend policy, whereas collateralizable assets have a large favourable impact. The results of research help businesses choose the right dividend policies. In order to protect prospective investors and ensure that they make the best investment decisions, companies must properly disclose their dividend payments and dividends per share.